2019
DOI: 10.1021/acscatal.9b03737
|View full text |Cite
|
Sign up to set email alerts
|

N-Oxyl Radicals Trapped on Zeolite Surface Accelerate Photocatalysis

Abstract: The zeolite materials have been industrially used in the thermal catalysis, but their function in photocatalysis has not been fully explored. Here we report that zeolites as supports could strengthen the radical formation after loading ferric oxide nanoparticles (FeO x /zeolite) under photoirradiation. Multiple theoretical and experimental studies demonstrate that the N-hydroxyphthalimide (NHPI) molecules could be trapped within the orifice of MFI zeolites via a sterically controllable adsorption, weakening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 35 publications
0
22
3
1
Order By: Relevance
“…Their combined XRD, UV–vis DRS, and ESR investigations revealed that photocatalytic activity is related to the content of iron-impurity, irrespective of zeolite properties. Under photoirradiation, the similar ferric oxide nanoparticles loaded with MFI zeolite could generate and stabilize N -oxyl radical formation, facilitating hydrocarbon oxidation into the corresponding ketones/carboxylic acids . Among other examples, analogous zeolite-mediated photocatalysts were used to treat volatile organic compounds (VOC), , degradation of organics diluted in water and air, photocatalytic reduction of CO 2 , and other relevant environmental applications. , …”
Section: Radical Chemistry In Zeolite Catalysismentioning
confidence: 99%
“…Their combined XRD, UV–vis DRS, and ESR investigations revealed that photocatalytic activity is related to the content of iron-impurity, irrespective of zeolite properties. Under photoirradiation, the similar ferric oxide nanoparticles loaded with MFI zeolite could generate and stabilize N -oxyl radical formation, facilitating hydrocarbon oxidation into the corresponding ketones/carboxylic acids . Among other examples, analogous zeolite-mediated photocatalysts were used to treat volatile organic compounds (VOC), , degradation of organics diluted in water and air, photocatalytic reduction of CO 2 , and other relevant environmental applications. , …”
Section: Radical Chemistry In Zeolite Catalysismentioning
confidence: 99%
“…On the other hand, natural minerals have high adsorption capacity, high thermochemical stability, low cost, convenient recycling, and rich content, which are good choices for the construction of macrosystems, such as kaolinite, [20] montmorillonite, [21] or zeolite. [22,23] Among them, vermiculite is a phyllosilicate mineral montmorillonite similar, which means a layer of the tetrahedral and octahedral ratio of 2 : 1 arrangement of composition, a thickness of about 1 nm or so, between the cell layer 2 is a layer of water molecules. Vermiculite has good cation exchange and adsorption properties, so it has a good application prospect in removing pollutants and the adsorption of heavy metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Addition of butylated hydroxytoluene (BHT) completely suppressed the oxidation (Table , entry 12). The in situ electron paramagnetic resonance (EPR) clearly demonstrated the formation of PINO radical in accordance with previous reports , (Figure a). Conversely, no PINO signal was observed, even with the good peroxide decomposition catalyst such as Ru­(acac) 3 , indicating PINO generation boosted by bisCu (Figure b).…”
mentioning
confidence: 99%
“…The Xu group used anthraquinone derivatives as the biomimetic SET reagent to accelerate the PINO-mediated oxidation of ethylbenzene . Notably, Xiao and Wang have both reported the innovative methods to achieve ambient oxidation of benzylic and cyclic C–H bonds, via stabilizing the photogenerated PINO radicals inside the FeO x /zeolite and on the surface of α-Fe 2 O 3 , respectively.…”
mentioning
confidence: 99%